2019
DOI: 10.1016/j.archoralbio.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in periodontal disease: Evidence from a literature review

Abstract: Objective: To summarize evidence and data in relation to the implications of autophagy in periodontal disease (PD) and describe potential nutraceuticals or pharmaceuticals able to modulate this subtype of cell death. Design: Literature searches of different electronic databases (Medline via PubMed, SCOPUS, Web of Science, and EMBASE) using appropriate keywords (e.g. periodontal disease, periodontitis, alveolar bone loss, periodontal infection, tooth loss, autophagy, programmed cell death, type 2 cell death) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 145 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…Until now, the significance of autophagy in periodontal diseases is not fully unraveled 11 . Autophagy may protect cells from apoptosis, increasing angiogenesis, while it may also trigger cell death, and facilitate immune evasion of bacteria 12 . Our present study indicated that NCOA4‐mediated ferritinophagy may increase free iron availability during inflammatory responses in host cells.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Until now, the significance of autophagy in periodontal diseases is not fully unraveled 11 . Autophagy may protect cells from apoptosis, increasing angiogenesis, while it may also trigger cell death, and facilitate immune evasion of bacteria 12 . Our present study indicated that NCOA4‐mediated ferritinophagy may increase free iron availability during inflammatory responses in host cells.…”
Section: Discussionmentioning
confidence: 59%
“…Autophagy is basically a cellular recycling pathway, and it also can defend host cells from invaded microbials by pathogen degradation 12 . Iron is critical to the survival of almost all living organisms; therefore, host cells may utilize iron that is stored in the ferritin when challenged by pathogens 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, disruption in the regulatory mechanisms of autophagy has been demonstrated in periodontitis ( Jiang et al, 2020 ). Meanwhile, numerous pharmaceutical and nutraceutical agents have been shown to modulate autophagy, thus serving as useful therapies for periodontitis ( Lorenzo-Pouso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recent studies found that autophagy protects PDL stem cells from apoptosis and promotes angiogenesis in the inflammatory microenvironment. 6,8 Autophagy helps eliminate periodontal pathogen infection and modulates the immune inflammatory response in periodontitis. 9 However, the precise mechanism by which autophagy is regulated under inflammatory conditions remains unclear.…”
Section: Introductionmentioning
confidence: 99%